OPTIMALISASI PEMANFAATAN GADGET PADA REMAJA UNTUK E-COMMERCE MELALUI SHOPEE AFFILIATE - Nadhiroh, Nadhiroh; Anggraini Kusumaningtyas; Choirul Amirudin (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
This article explores the use of gadgets among teenagers for E-Commerce through Shopee Affiliate. Technological developments bring many changes. One of them is in the field of digital marketing or digital markets which are usually called e-commerce. The development of the e-commerce market in Indonesia continues to increase every year. During the pandemic, digital access is increasingly being used because circumstances limit face-to-face activities. Many consumers choose to shop online and rely on digital shopping platforms to meet their needs. E-commerce is one of the people's options for searching for and buying products. The research method in carrying out this research uses a qualitative approach by analyzing descriptive data. Data was collected through interviews, observations and related supporting data such as photos, articles, books and other internet sources. This socialization activity was carried out in the Keden, Sidoharjo area and the targets who took part in this activity were teenagers aged 15-18 years. The identification results show that many people do not know about e-commerce. The evaluation results from this activity can provide insight, knowledge and inspiration. After holding this outreach regarding e-commerce, it is hoped that it will be useful for teenagers in the Keden area in order to optimize the use of gadgets for teenagers for productive things. The teenagers are expected to be able to earn an independent income even though they are still in school.